Membumikan Lesson Study Dalam Meningkatkan Kemampuan Mengajar Berbasis STEM Bagi Guru Matematika SMK Negeri 1 Singkep Kabupaten Lingga - Hadi, Samsul (Syntax Idea, 2020)
This study aims to apply lesson studies to improve STEM-based teaching skills for teachers of SMK Negeri 1 Singkep. The application of lesson studies is expected to be useful in improving teaching skills after the implementation and culture of lesson studies among mathematics teachers. In this study, the researcher as the principal with a mathematics teacher background implemented learning through workshops as a practice of implementing and understanding teaching teachers. With STEM-based learning, it is hoped that teachers can carry out discussions in planning lessons, implement teacher learning models in teaching and be able to reflect on learning. The research used school action based on Kemmis & Taggart which consisted of 2 cycles starting with planning, acting, observing and reflecting. As research subjects are teachers of SMK Negeri 1 Singkep which consists of 28 teachers. From the results of this study, it was found that through the application of this method, (1) teachers can improve STEM-based teaching skills, (2) teachers can improve skills in making observations, and (3) teachers can increase knowledge in terms of adding insight into learning methods in class . Based on the results of data analysis, it shows that this method is effective for improving the teaching ability of STEM-based teachers, in the first cycle the teacher's average ability was 70.82 and increased to 78.88 in the second cycle, an increase of 8.06 was quite significant. And there was a significant increase in 3 mathematics teachers. Thus the principal is sought to be able to provide intensive, directed and sustainable coaching for teachers in teaching, because lessons can provide experience for teachers to always reflect on the learning that has been carried out as a reference for teachers in carrying out learning effectively and effectively in accordance with the objectives set in curriculum.